Evaluation of Myelin Phagocytosis by Microglia/Macrophages in Nervous Tissue Using Flow Cytometry. Issue 3 (9th March 2021) - Gómez‐López, Ariadna Regina; Manich, Gemma; Recasens, Mireia; Almolda, Beatriz; González, Berta; Castellano, Bernardo
Abstract: Determination of microglial phagocytosis of myelin has acquired importance in the study of demyelinating diseases. One strategy to determine microglial phagocytosis capacity consists of assaying microglia with fluorescently labeled myelin; however, most approaches are performed in cell culture, where microglia usually show important phenotypic differences compared with in vivo conditions. In this article we describe an adapted flow cytometry protocol to assay myelin phagocytosis by microglia obtained directly from in vivo tissue of the central nervous system. Key steps for a first analysis of phagocytic microglia are provided. Additionally, we describe how to fluorescently label myelin using a pH‐sensitive tag, pHrodo™ Green STP Ester. © 2021 Wiley Periodicals LLC. Basic Protocol : Assay for determination of myelin phagocytosis by microglia/macrophages using flow cytometry Support Protocol 1 : Conjugation of isolated and purified myelin with pHrodo Green STP Ester Support Protocol 2 : Quantification of phagocytic cell number by flow cytometry